The Iraq War ten years on: assessing the fallout - Fawcett, Louise L'Estrange (International affairs, 2013)
Assessing the long-term fallout from the 2003 Iraq War from three perspectives-the state, regional and international-this article argues that the war generated a series of changes that have had a central impact on the political evolution and international relations of the Middle East, though not in the manner anticipated by either its supporters or critics. The war and its consequences, which have become merged with developments surrounding the Arab Spring uprisings, which started at the end of 2010, have contributed over the long term to the acceleration of popular demands for the greater liberalization of politics, to shifts in the regional balance of power and to international realignments. Authoritarian regimes across the region have been increasingly challenged; there are new sectarian divides; Iran has been empowered by the demise of its old rival Saddam Hussein; new ‘pivotal’ states like Saudi Arabia and Turkey have emerged; and western powers have had to review their policy prescriptions and assumptions of regional predominance. The new regional order is both fragile and contested. Taking a long view of the Iraq War on its tenth anniversary is important and relevant to understanding contemporary developments in the region-whether in Syria or elsewhere-and serves to highlight patterns of continuity as well as change. Given the continuing violence and bloodshed in Iraq itself, it also offers some important lessons to regional and external powers about the perils of intervention. (International Affairs (Oxford) / SWP)